Using Educational Technology to Reduce Learning Loss During the COVID-19 Pandemic - Bambang Gulyanto; Dewi Purnama Sari (STAI Hubbulwathan Duri, 2023)
The purpose of this study is to describe how educational technology was used to minimize learning loss at Senior High School. The COVID-19 pandemic has had a negative impact on education in schools. The ability of students to achieve competence and learning objectives is weaker than before. This phenomenon is termed